Response of Archaeal Communities in Beach Sediments to Spilled Oil and Bioremediation - Röling, Wilfred F. M. (American Society for Microbiology, 2004)
While the contribution of Bacteria to bioremediation of oil-contaminated shorelines is well established, the response of Archaea to spilled oil and bioremediation treatments is unknown. The relationship between archaeal community structure and oil spill bioremediation was examined in laboratory microcosms and in a bioremediation field trial. 16S rRNA gene-based PCR and denaturing gradient gel analysis revealed that the archaeal community in oil-free laboratory microcosms was stable for 26 days. In contrast, in oil-polluted microcosms a dramatic decrease in the ability to detect Archaea was observed, and it was not possible to amplify fragments of archaeal 16S rRNA genes from samples taken from microcosms treated with oil. This was the case irrespective of whether a bioremediation treatment (addition of inorganic nutrients) was applied. Since rapid oil biodegradation occurred in nutrient-treated microcosms, we concluded that Archaea are unlikely to play a role in oil degradation in beach ecosystems. A clear-cut relationship between the presence of oil and the absence of Archaea was not apparent in the field experiment. This may have been related to continuous inoculation of beach sediments in the field with Archaea from seawater or invertebrates and shows that the reestablishment of Archaea following bioremediation cannot be used as a determinant of ecosystem recovery following bioremediation. Comparative 16S rRNA sequence analysis showed that the majority of the Archaea detected (94%) belonged to a novel, distinct cluster of group II uncultured Euryarchaeota, which exhibited less than 87% identity to previously described sequences. A minor contribution of group I uncultured Crenarchaeota was observed.